A short review on synthesis and characterisation of nano SiO2 / TiO2 composite for insulation application / Nurul Farrahani Azlan ... [et al.] - Azlan, Nurul Farrahani; Akhbar, Suffiyana; Hanipah, Suhaiza Hanim; Sharudin, Rahida Wati (Universiti Teknologi MARA, 2021)
Silica dioxide (SiO2) and titanium dioxide (TiO2) are nanoparticle fillers that are widely incorporated into polymer matrix for thermal insulation application. Combination of both fillers in producing polymer nanocomposite is interesting to review. This paper reviews on the current and recent research on the method to incorporate the SiO2/TiO2 nanoparticles as the fillers into various polymer matrix such as direct mixing, intercalation, sol-gel and in situ polymerisation as well as the effect of nanofillers on the thermal properties, morphology studies, rheology behaviour, mechanical property, and conductivity (thermal and electrical) of the SiO2/TiO2 polymer nanocomposites. This paper also reviews the effect of SiO2/TiO2 nanoparticles to the polymer nanocomposites in term of dielectric properties as a potential electrical insulation material. SiO2 nanoparticles presented to be the best filler to enhance the dielectric properties compared to the TiO2. When both of nanofillers are incorporated into the polymer matrix, a better result in term of mechanical, thermal, and electrical insulation properties are produced.